Struggles in Cultural Construction by Ethnic Groups in the USA - Lolowang, I S (Universitas Negeri Manado, 2018)
This article discusses about the struggles in cultural construction by some ethnic groups. These groups are attributed to their race and class as well. Through blending and negotiation experiences, the ethnic groups struggle to invent their identity and power in facing the dominant culture, the white people. They have to face both the external and the internal factors of their coexistence in the society. The groups discussed are the Mexican-American or the brown people, the African-American or the black, and the Asian-American or the yellow one.Keywords: cultural construction, Mexican-American, AfricanAmerican, Asian-American, color people